Mozart's Piano Concerto in D Minor, K. 466: Questions of Significance - Cheng, Shirley Wai Yee. (2008)
My thesis begins from the observation that Mozart wrote only two of his 27 piano concertos in the minor key. This very small output of minor key piano concertos seems unusual, unless it is simply the result of the popular use of the major key in compositions written in the 18th century. Still however, the fact that Mozart wrote these concertos in the minor key suggests that there might be some special significance associated with the choice of key.